Effects of repetitive thermal loads on microstructure and mechanical properties of potassium-doped tungsten alloy as plasma facing material - Hui Wang; Zhuo-Ming Xie; Da-Huan Zhu; Mu-Lan Yu; Yin-Juan Fu; Rui Liu; Xian-Ping Wang; Qian-Feng Fang; Chang-Song Liu; Xue-Bang Wu (Nuclear Fusion)
Plasma-facing materials (PFMs) in fusion reactors are inevitably subjected to severe thermal shocks, making the performance of tungsten (W)-based PFMs under repetitive high thermal loads critical for the long-term stable operation of fusion reactors. Potassium-doped W (W–K) alloys present a promising alternative for PFMs due to their superior thermal and mechanical properties. However, unlike conventional second-phase particles, the K bubbles within W alloys do not form distinct phase interfaces with the W matrix, leaving their behavior poorly understood under transient thermal loads. This study investigates the effects of cyclic thermal loads on the evolution of K bubbles and mechanical properties of W–K alloys. Thermal load tests were conducted with a single-pulse duration of 1 s at absorbed power densities of 10, 13, 15 and 20 MW m ^−2 for 50 cycles at room temperature. Tensile test results indicate an unexpected increase in ductility in the W–K alloy while maintaining high strength after exposure to thermal loads at 10 and 13 MW m ^−2 . Microstructural analyses reveal that K-tubes with large aspect ratios rupture due to Rayleigh instability, leading to the formation of well-dispersed, nano-sized polyhedral K bubbles. These fine K bubbles, with abundant dislocations at their interfaces, serve as dislocation sources, enhancing ductility. The present work offers a physical depiction of K bubble evolution in W–K alloys under thermal fatigue conditions relevant to fusion environments, suggesting a strategy for optimizing their mechanical properties by promoting the formation of nano-sized, interface-dislocation-decorated K bubbles.